Synthesis and cellular effects of novel 1,3,5-triazine derivatives in DLD and Ht-29 human colon cancer cell lines - Wróbel, Agnieszka (Invest New Drugs, 2019)
This study provides new information on the cellular effects of 1,3,5-triazine nitrogen mustards with different peptide groups in DLD and Ht-29 human colon cancer cell lines. A novel series of 2,4,6-trisubstituted 1,3,5-triazine derivatives bearing 2-chloroethyl and oligopeptide moieties was designed and synthesized. The most cytotoxic derivative was triazine with an Ala-Ala-OMe substituent on the ring (compound 7b). This compound induced time- and dose-dependent cytotoxicity in the DLD-1 and HT-29 colon cancer cell lines. The triazine derivative furthermore induced apoptosis through intracellular signaling pathway attenuation. Compound 7b may be a candidate for further evaluation as a chemotherapeutic agent against colorectal cancer.